Synergistic Effects of Nano Titanium Dioxide and Nano Zinc Oxide on the Physical and Rheological Properties of Asphalt Binder - Obaidi, Hadel; Mohammad, Hussein K.; Albayati, Amjad H. (Civil Engineering Journal, 2026)
Enhancing asphalt binder performance against anticipated distresses is a critical focus in pavement engineering. This study investigates the synergistic influence of nano titanium dioxide (NT) and nano zinc oxide (NZ) on asphalt binder performance. Nine NT:NZ combinations (1:1 to 3:3) were prepared with 1–3% by binder weight, in addition to a reference binder (RB). The performance test program included; conventional tests (penetration, softening point, viscosity, and ductility), Dynamic Shear Rheometer (DSR) for performance grading, Multiple Stress Creep Recovery (MSCR) for rutting evaluation, and Linear Amplitude Sweep (LAS) for fatigue resistance. Furthermore, Statistical analysis (ANOVA) was performed to determine the significance of nanomaterial interactions, and a cost–performance evaluation assessed economic feasibility. The results revealed that the combined use of these types of NM increased binder stiffness and resistance to aging. Additionally, the high-temperature PG grade increased from 70°C to 76°C for all NM-modified asphalt binders, except for the combinations of 1% NT and 1% NZ, as well as the (1:2) binder. On the other hand, MSCR results showed a reduction of up to 32% in non-recoverable creep compliance (Jnr3.2), whereas the LAS test verified extended fatigue life at a 2.5% strain level for low dosages of the NM combination, i.e., (1:1). The 1:1 NT:NZ blend exhibited the highest cost–performance efficiency, providing a balanced improvement in rutting and fatigue resistance. Overall, the synergistic incorporation of NT and NZ significantly enhanced the binder performance, offering practical insights for selecting nanomaterials in sustainable pavement engineering.